Improving Student Reflective Thinking Skills by Using Flipbooks in Australian and Oceanian History Learning - Brigda Intan Printina; Veronica Yovita Indaryadi (JUPIIS: JURNAL PENDIDIKAN ILMU-ILMU SOSIAL, 2022)
Today's Learning Demands Technological Transformation, However, The Practice Of Reflective Thinking Has Become One Of The Learning Traditions And Hallmarks Of Jesuit Education. Learning History Australia & Oceania Has Learning Outcomes, One Of Which Is Opening Up Insights Into New Cultures And Civilization Patterns Of Australian And Island Communities Around The Pacific. Not Only Exploring The Context But Also Being Able To Explore The Paradigm Of Reflective Thinking Of Students As An Analysis Of Solving The Nation's Problems. Students Need To Train Themselves In Reflective Thinking Because It Is Important To Analyse The Context Of Australia's Developmental Events, And Then How To Solve The Problems Of A Dynamic Societal Structure Fighting For Humanity And Well-Being. With Reflective Thinking Exercises In This Course, Students Will Be Accustomed To Analyzing And Synthesizing The Offers Of Solving The Problems Of Nations To Face The Challenges Of Life In This Century. One Of The Learning Tools Used To Explore Students' Reflective Thinking Skills In Australian And Oceania History Lectures Is The Use Of Flipbooks. This Study Aims To Decipher: 1) The Dynamics Of Flipbook-Based Student Reflective Thinking In Australian And Oceania History Learning; 2) The Limitations And Advantages Of Implementing Flipbook-Based Student Reflective Thinking Dynamics In Australian And Oceania History Learning; 3) Evaluation Of Flipbook-Based Student Reflective Thinking Dynamics In Australian And Oceania History Learning. The Method Used Is Qualitative Research With A Case Study Approach. Data Collection Through Observation, Depth Interviews And Literature Studies. Meanwhile, The Benefit Of This Research Is To Explore The Dynamics Of Reflective Thinking Of Students In The Australian History & Oceania Course Based On Flipbook Facilities.